Patient-Tailored, Home-Based Non-invasive Brain Stimulation for Memory Deficits in Dementia Due to Alzheimer's Disease - Bréchet, Lucie; Yu, Wanting; Biagi, Maria Chiara; Ruffini, Giulio; Gagnon, Margaret; Manor, Brad; Pascual-Leone, Alvaro (Frontiers in Neurology, 2021)
Alzheimer’s disease (AD) is an irreversible, progressive brain disorder that can cause dementia (Alzheimer’s disease-related dementia, ADRD) with growing cognitive disability and vast physical, emotional and financial pressures not only on the patients but also on caregivers and families. Loss of memory is an early and very debilitating symptom in AD patients and a relevant predictor of disease progression. Data from rodents, as well as human studies, suggest that dysregulation of specific brain oscillations, particularly in the hippocampus, is linked to memory deficits. Animal and human studies demonstrate that non-invasive brain stimulation (NIBS) in the form of transcranial alternating current stimulation (tACS) allows to reliably and safely interact with ongoing oscillatory patterns in the brain in specific frequencies. We developed a protocol for patient-tailored home-based tACS with an instruction program to train a caregiver to deliver daily sessions of tACS that can be remotely monitored by the study team. We provide a discussion of the neurobiological rationale to modulate oscillations and a description of the study protocol. Data of two patients with ADRD who have completed this protocol illustrate the feasibility and promise of the approach and provide pilot evidence on the safety and efficacy of the remotely-monitored, caregiver-administered, home-based tACS intervention. These findings encourage the pursuit of a large, adequately powered, randomized controlled trial of home-based tACS for memory dysfunction in ADRD.